Improving Health, Nutrition and Population Outcomes in Sub-Saharan Africa : the Role of the World Bank. (World Bank e-Library., 2005)
"Sub-Saharan Africa continues to struggle with the challenges of communicable disease, malnutrition, and high fertility. Because health, nutrition, and population greatly affect poverty reduction efforts, the World Bank has a role to play in responding to these challenges. Improving Health, Nutrition, and Population Outcomes in Sub-Saharan Africa explains how that role is shaped by three factors - countries' setting of priorities, provision of resources through specific programs, and the Bank's expertise in analysis, knowledge transfer, and policy advice. The authors argue that the Bank can have the greatest impact by coordinating its efforts with partners and by focusing on its areas of comparative advantage: macroeconomics and health, multisectoral action for health, and health sector reform (systems and financing)."